Association between VEGF gene polymorphisms and in-stent restenosis after coronary intervention treated with bare metal stent - Bagyura, Zsolt; Hirschberg, Kristóf (Disease markers, 2017)
Background. In-stent restenosis (ISR) is the gradual narrowing of the vessel lumen after coronary stent implantation due to the increase in vascular smooth muscle cell proliferation. Vascular endothelial growth factor (VEGF) protein plays an important role in this process. Our aim was to analyze the association of single nucleotide polymorphisms of the VEGF gene (rs2010963 and rs6999447) with the occurrence of ISR after coronary artery bare metal stent (BMS) implantation. Methods. 205 patients with a history of BMS implantation and a repeated coronarography were prospectively enrolled. Patients were assigned to diffuse restenosis group () and control group () and VEGF genotypes were determined. Results. Diffuse ISR was significantly more frequently observed in patients with homozygous normal genotype of rs2010963 polymorphism, and this polymorphism was independently associated with diffuse ISR. Conclusions. RS2010963 is associated with higher incidence of development of diffuse coronary ISR in patients treated with BMS implantation.